Characterization of a putative periplasmic transport system for octopine accumulation encoded by Agrobacterium tumefaciens Ti plasmid pTiA6. - Valdivia, R H (1991)
Neoplastic crown gall tumors incited by Agrobacterium tumefaciens release novel amino acid or sugar derivatives known as opines, whose synthesis is directed by genes transferred to plant cells. Agrobacterium cells can transport and catabolize these compounds as sources of carbon and nitrogen. This article describes a region of the pTiA6 plasmid which is required for catabolism of the opine octopine and whose transcription is induced by octopine. This region of the plasmid contains four open reading frames, occQ, occM, occP, and occJ, which show homology to the family of so-called shock-sensitive permeases. TnphoA mutagenesis demonstrated that the OccJ and OccM proteins lie fully or partly in the periplasmic space. The OccJ protein was identified by electrophoresis and found to be fully localized in the periplasmic space. When these proteins were expressed in Escherichia coli, radiolabeled octopine became cell-associated.